THE STUDY OF REPRODUCTIVE BEHAVIOR AND EMBRYONIC DEVELOPMENTS OF NEOPOMACENTRUS CYANOMOS. - Loh, Kar-Hoe; Cheng, You-Hua; Chen, Hong -Ming (Malaysian Journal of Science, 2013)
Regal demoiselle Neopomacentrus cyanomos belongs to the subfamily Pomacentrinae of family Pomacentridae. 50 individuals of this species were reared in laboratory aquaria to observe reproductive behaviors. Before courtship, the dominant male chose suitable substrate and cleared up it frequently. Among one reproductive affair, a male N. cyanomos mated with 3-4 females, and constantly moved outside of spawning substrate area to attract females, its black body color occur to grey stripes at that time. After spawning, the male protected fertilized eggs until hatching. During the 47 days of records dating from 21 June to 6 August 2004, the regal demoiselle ovulated five times, and mature female spawned once every 5~13 days (8 ± 4 days), each time produced about 3210~3560 eggs. These adhesion demersal eggs were trans- lucent and gourd form. Length of eggs was 1.27 ± 0.06 mm (n = 66), egg diameter was 0.5 ± 0.02 mm, length of yolk-sac was 0.75 ± 0.03 mm and maximum oil globule was 0.17 ± 0.02 mm. The developments of cleavage, morula, gastrula stage, and embryonic body were recorded. After 19.5 hours, optic vesicles and auditory vesicles were visible sequentially, and the embryo’s somites turn obviously. After 35 hours, the embryo’s head turned to the top position of egg. Through 84 hours, eyes turn blackish. After 108 hours, larvae broke the eggs and hatched out. The larval body length was 2.85 ± 0.12 mm (n =10). (Keywords: Neopamacentrus cyanomos, reproductive behavior, embryonic development, larva)